Effectiveness Of Health Education Package On Practice Regarding Care Of Preterm Baby Among Preterm Mothers At Selected Hospitals - Nidhi, Nidhi; Modi, Prashant (Journal of Neonatal Surgery, 2025)
Background: it is clearly stated that most of the preterm babies are born yearly and they are exposed to number of neonatal problems. It is essential that antenatal period education is important and precaution. They need special care to improve the health status of preterm babies. Material and methods: A pre-experimental research design was used one group pretest and posttest research design. A total of 50 preterm mothers were selected by convenience sampling technique, practice checklist was used for data collection. Descripotive statistics, mean, SD and t test,chisquare test were used for analysis. Result: The pretest and posttest level of practice regarding care of preterm baby among mothers in pretest 38(76%) were poor practice,12(24%) were good practice. In posttest level 36(72%) were good practice and 14(28%) were poor practice regarding care of preterm baby among mothers. that the pretest means score practice regarding care of preterm baby mean and SD 1.941±0.6214 and posttest mean score of practice regarding care of preterm baby among mothers 1.461±0.9731.The calculated paired t value of t= 18.041 was found to be statistically significant at p<0.05 level this clearly indicated that health education programme found to be effective in management of care of preterm baby among women. The association between pretest level of practice regarding care of preterm baby among women with their selected demographic variables. Education status of mothers had significant association with pretest level of practice p<0.05 level. Demographic variables like Age, religion, occupation, family monthly income, type of family and source of information no significant association with pretest level of practice. This indicated that health education was significantly effective with increase practice regarding care of preterm baby among women. Conclusion: In this study shows that health education was found to be effective in improving the practice on care of preterm baby and improve the practice of antenatal mothers.